2010
DOI: 10.1002/mame.201000162
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Thermal Behavior of Poly(propylene) by Addition of Spherical Silica Nanoparticles

Abstract: Spherical silica nanoparticles were mixed with a PP matrix and the thermal behavior of the nanocomposites was studied. The nanocomposites presented drastic improvements in the degradation behavior under thermo‐oxidative conditions, showing complex multistep processes. Under inert conditions the improvements were lower. Our results indicate that mechanisms based on the labyrinth effect, nanoconfinement or trapping model, are not able to explain the whole enhanced thermal stability in these nanocomposites. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 33 publications
(75 reference statements)
7
52
0
Order By: Relevance
“…The amount of residue obtained under air at 600 C is the same than that obtained under nitrogen for all samples, which suggests that no char is formed with the addition of pure and modified silicas. In their studies, Palza et al [18] confirm that with 5 wt% of spherical silica nanoparticles, the thermal degradation of PP is considerably improved under air (increase of pMLR temperature of 70 C) in comparison to tests carried out under nitrogen (increase of pMLR temperature of 10 C). The authors show that the thermal degradation is slightly delayed by adding a compatibilizer (PP-g-MA) (z10 C and z30 C under inert and oxidative atmosphere respectively) which may prove that the dispersion plays a role on the thermal stability.…”
Section: Thermal Behaviormentioning
confidence: 87%
“…The amount of residue obtained under air at 600 C is the same than that obtained under nitrogen for all samples, which suggests that no char is formed with the addition of pure and modified silicas. In their studies, Palza et al [18] confirm that with 5 wt% of spherical silica nanoparticles, the thermal degradation of PP is considerably improved under air (increase of pMLR temperature of 70 C) in comparison to tests carried out under nitrogen (increase of pMLR temperature of 10 C). The authors show that the thermal degradation is slightly delayed by adding a compatibilizer (PP-g-MA) (z10 C and z30 C under inert and oxidative atmosphere respectively) which may prove that the dispersion plays a role on the thermal stability.…”
Section: Thermal Behaviormentioning
confidence: 87%
“…[19][20][21][22][23] Moreover, the nanocomposites may show additional specific properties if the fillers are properly designed, i.e. 37 For this reason, inorganic nanoparticles bearing a polymer stabilizer shell can better disperse in PLGA matrix and reduce the phase separation processes, 38,39 and eventually can affect the polymeric matrix degradation and hence the silver release. 24 Metal nanoparticles have attracted great interest for their unique optical, electrical, catalytic, and biomedical properties.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested there was synergistic effect for the DOPO-immobilized SiO 2 nanoparticles. It is known that SiO 2 can improve stability due to physical effect [42, 43]. This could be explained by the fact that DOPO-immobilized SiO 2 nanoparticles could induce carbonization and form thermally-stable char, and therefore to reduce releasing rate of degradation volatiles [20, 44].…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the silanol groups on the surface of SiO 2 could catalyze the thermal degradation [38, 42, 43], thus the apparent activation energies were lower than that of pure PP. The degradation products could be adsorbed on the surface of the SiO 2 nanoparticles [1, 42], so the apparent weight loss was slow. For the PP/SiO 2 –WD70–DOPO (5 wt%) nanocomposite, E α increased linearly as the degradation proceeded, which was very different from that of PP and PP/SiO 2 nanocomposite (5 wt%).…”
Section: Resultsmentioning
confidence: 99%